Workplace bullying among doctors in residency training: a scoping review - Fatmawati, Lady Farah; Siregar, Kemal Nazaruddin (Universitas Gadjah Mada, 2024)
Purpose: This study aims to determine the prevalence, risk factors, impacts, and response types to workplace bullying among resident doctors. Methods: The study was conducted using the scoping review method. An online search was performed across five databases, MEDLINE [PubMed], Cochrane Library, APA PsycArticles, Scopus, and Science Direct, using keyword developments from Medical Subheadings (MeSH). The selected articles were those published from 2013 to 2024. Results: A total of 1,402 articles that discussed workplace bullying were identified, and after screening based on inclusion and exclusion criteria, 19 articles were selected. The prevalence of workplace bullying ranged from 13% to 89% across various specialties. Additionally, a significant relationship was found between specialization type, residency year, age, gender, skin color, work shifts, organizational climate, and the mental condition of the resident doctors with the incidence of workplace bullying. Resident doctors who were victims of bullying were at risk of experiencing cognitive disorders, fatigue, job dissatisfaction, sleep difficulties, performance decline, weight changes, and even suicidal thoughts. Victims of bullying tended to respond to the behavior by sharing their experiences with family, friends, or close ones. Conclusions: Bullying among resident doctors shows a relatively high prevalence. Future research is expected to develop a confidential bullying reporting system as an initial mechanism for controlling workplace bullying.